Effect of a proprioceptive balance board training program on functional and neuromotor performance in volleyball players predisposed to musculoskeletal injuries - Zarei, M.; Soltani, Z.; Hosseinzadeh, M. (Sport Sciences for Health, 2022)
Background The Verhagen volleyball-specific neuromuscular exercise training (NEMEX) program has already been recommended for preventing ankle sprain recurrences in volleyball players; however, the effect of this proprioceptive balance board training program as a training intervention on improving the functional movement characteristics of these players has received less attention.